2017
DOI: 10.1002/app.46146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of gamma and ion beam irradiation of polymeric nanocomposite on electrical conductivity

Abstract: Poly(vinyl alcohol) (PVA) was used to prepare nanocomposites of multi-wall carbon nanotubes (MWCNT) and functionalized carbon nanotubes (MWCNT-NH 2 ) in existence of 2-carboxyethyl acrylate oligomers (CEA). Radiation-induced crosslinking of the prepared matrix was carried out via gamma and ion beam irradiation. A comparative study of gamma and ion beam irradiation effect on the electrical conductivity of nanocomposite was conducted. The gelation of the gamma irradiated matrix outperforms the ion beam irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 27 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…In previous investigations, the influences of blending PVA with different ratios of plasticizers on electrical, structural, and mechanical properties of the membranes were examined. The studies demonstrated that the addition of plasticizers to PVA enabled the control of its electrical conductivity and decreased the interaction among the macromolecules that increased the flexibility of its membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous investigations, the influences of blending PVA with different ratios of plasticizers on electrical, structural, and mechanical properties of the membranes were examined. The studies demonstrated that the addition of plasticizers to PVA enabled the control of its electrical conductivity and decreased the interaction among the macromolecules that increased the flexibility of its membranes.…”
Section: Introductionmentioning
confidence: 99%
“…12 The analysis enables identification of capacitance and charge transfer for composite membranes, the influence of blocking electrodes, the effect of grain boundaries, and so forth. 13 In previous investigations, 1,2,14,15 the influences of blending PVA with different ratios of plasticizers on electrical, structural, and mechanical properties of the membranes were examined. The studies demonstrated that the addition of plasticizers to PVA enabled the control of its electrical conductivity and decreased the interaction among the macromolecules that increased the flexibility of its membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The samples preparation method is as previously described by the authors . The 10 wv −1 % PVA solution was prepared by dissolving it in water for 6 h at 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The samples preparation method is as previously described by the authors. 21 The 10 wv 21 % PVA solution was prepared by dissolving it in water for 6 h at 80 8C. MWCNT and MWCNT-NH 2 nano-filler were mixed with the PVA/CEA solution with the aid of the concentration 0.5 wv 21 % surfactant, the detailed method was described in Refs.…”
Section: Methodsmentioning
confidence: 99%
“…28,32 The dose-dependent further improvement is probably due to enhancement of the electrical conductivity caused by the increased crosslinking density of the SPVA binders at the higher dose (leading to the more tightly bound activated carbons). 33,34 Furthermore, the activated carbon content-dependent improvement result could be ascribed to increment in the surface area and electrical conductivity facilitating the electrochemical processing. 15,16,35 Therefore, the specic capacitance of the carbon electrode can easily be improved by combining hydrophilic SPVA with quick electron-beam irradiation-induced crosslinking at room temperature, which is benecial for mass production.…”
Section: Electrochemical Properties Of Spva-based Carbon Electrodesmentioning
confidence: 99%